Macronutrients variability in lateritic soil and effects of organic amendment contents on mango cv harumanis - Mohamad Shahidin, Nurhaliza (2016)
Mango (Mangifera indica L.) is one of the 16 fruits that have been highlighted for the agricultural development in the Third National Agricultural Policy (NAP3) by Malaysian Ministry of Agriculture in 1999. Currently, production of Harumanis mango was unable to cater the increasing demand in local and international markets. Cultivation of Harumanis mango on marginal soils such as lateritic soils is quite challenging as the information regarding mango cultivated on lateritic soil is very scarce since this cultivar is mostly cultivated on soil with pH greater than 7. Application of chemical fertilizer (CF) in mango cultivation area over the years has worsened the acidity problems of lateritic soil under humid tropical climate. Application of chicken manure (CM) compost into lateritic soil could reduce the level of soil acidity and enhances the soil chemical properties. Three field experiments have been conducted from January 2014 until June 2015 in mango cultivation area located at Universiti Teknologi Mara (UiTM) Perlis Campus (N 06.45427°; E 100.28352°) cultivated with Mangifera indica L. cv. Harumanis (MA 128) aged 5 years old on lateritic soil (Terap Series). Experiment 1 was implemented with the objectives i) to determine variability of selected soil chemical properties in vertical and horizontal direction and ii) to evaluate correlation between the selected chemical properties of lateritic soil. The objective of experiment 2 was to assess temporal variations in chemical properties of lateritic soil and foliar of mango with respect to plant phenological stage (PPS) (day of sampling) and slope position. The experiment 3 was implemented to evaluate the effects of chicken manure (CM) compost application on the selected soil chemical properties and macronutrients concentration in mango leaf and its effects on mango yield. All data were analysed using Analysis of Variance (ANOVA) and means separation were conducted using Tukey’s Honestly Significant Difference (HSD) test (p=0.05) using SAS Ver. 9.3. Pearson’s correlation analysis was also conducted by SAS Ver. 9.3. Experiment 1 was divided into vertical and horizontal variability study of the selected soil chemical properties. Soil samples were collected from nine soil pits at 0-15 cm, 15-30 cm, 30-45 cm and 45-60 cm depth for vertical variability study. For the horizontal variability study in 0.29 ha study plot, 50 topsoil (0-15 cm) samples were obtained by systematic sampling scheme. Results obtained in this study revealed that soil depth significantly (p≤0.05) affected soil pH, organic carbon (C), total nitrogen (N), carbon to nitrogen (C/N) ratio, available phosphorus (P), exchangeable potassium (K), magnesium (Mg) and aluminium (Al), and cation exchange capacity (CEC). Significant differences (p≤0.05) were also shown in clay and sand content by soil depth. Moderate variability indicated by coefficient of variation (CV) that ranged between 13.74% and 48.19% were found in organic C, total N, available P, exchangeable K, Ca, Mg and Al and base saturation in horizontal variability study. Soil organic C, total N and C/N ratio of topsoil in both vertical and horizontal variability study showed positive correlation greater than 70%. Exchangeable Al was negatively correlated (r > 40%) with available P, exchangeable K and Ca in horizontal direction. The experimental design used in experiment 2 was Randomized Complete Block Design (RCBD) with repeated measurement. Two independent variables in this experiment were plant phenological stage (PPS) (day of sampling); first flowering (0 day), fruiting (90 days), flushing (180 days), end of flushing (270 days) and second flowering (360 days); and slope position; upper, middle and lower. A total of 60 topsoil (0-15 cm) samples and 48 leaf samples were collected. The study results showed that soil pH, total N, available P, CEC, base saturation and exchangeable bases (K, Ca and Mg) as well as N, P, K, Ca and Mg content in the leaf were significantly (p≤0.05) affected by single factor of PPS (day of sampling). Slope position single factor were also significantly (p≤0.05) affected the exchangeable Ca, Mg and Al, CEC and base saturation as well as N and K content in the leaf. It was found that leaf N content was the only variable exhibited significant (p≤0.05) interaction effects between PPS (day of sampling) and slope position. The fertilizer treatments in experiment 3 consisted of a uniform rate (3.5 kg tree-1) of NPK Blue fertilizer (12:12:17:2) in combination with five rates of CM compost (0, 4, 8, 12 and 16 kg tree-1) with five replications which was laid out in Latin Square Design. Fertilizer was applied in two split application using pocket method in 15 cm depth. Soil and leaf sampling were conducted on 90, 180 and 270 days after the first fertilization. Yield parameters data were collected before and after fertilizer treatments, in year 2014 and 2015, respectively. The experiment results revealed that soil pH and exchangeable K, Ca and Mg in 0-15 cm and 15-30 cm soil depth has increased significantly (p≤0.05) after nine months of fertilization. However, there was no significant (p>0.05) effects of the fertilizer treatments in CEC for both soil depths. Significant (p≤0.05) effects were found in leaf Ca content whereas, N, P, K and Mg content in the leaf and yield parameters were not significantly (p>0.05) affected by the fertilizer treatments. The greatest increment in soil pH and exchangeable bases (K, Ca and Mg) was shown by the treatment of 16 kg tree-1 CM compost combined with 3.5 kg tree-1 CF. Based on the findings, variability of selected soil chemical properties in vertical and horizontal direction in the respected area occurs due to the combined effects of undulating landform, soil management practices (application of fertilizer and pesticides), clay content and non-uniform availability of soil nutrients. It was found that PPS (day of sampling) and slope position single factor has resulted in variation of the selected soil chemical properties and macronutrients content in leaf of Harumanis mango. Application of different rates of CM compost combined with CF has significantly (p≤0.05) enhanced the soil chemical properties in the study area. The recommended rate for increasing soil pH, exchangeable bases (K, Ca and Mg) and fruit yield on lateritic soil (Terap Series) of the respected area is combination of 16 kg tree-1 CM compost with 3.5 kg tree-1 CF.